Penguatan Ekosistem Bisnis melalui Digitalisasi Produk UMKM Solusi Berkah Miliyarder - Salsabila, Eisa Aulia; Putri, Eka Aprilia Yasinta; Ismiati, Eny Dwi Ayu; Afifah, Fajar Dwi Nur; Nuryani, Efi (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The rapid development of digital technology presents new opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their market reach. Solusi Berkah Miliyarder, an MSME located in Kediri, East Java, specializes in selling British Propolis. However, limited access to digital marketing has hindered its business growth. This community service program aimed to enhance the competitiveness of Solusi Berkah Miliyarder through the creation of an online catalog. The method used was Community-Based Research (CBR), involving training, mentoring, and implementation of a digital catalog via a dedicated website. The results showed a 30% increase in product sales and a wider market reach within the first month of implementation. Additionally, the MSME owners gained essential skills in managing online marketing independently. This program highlights the importance of digital transformation for MSMEs to thrive in a competitive business environment.